The upsizing of the São Tomé seed dispersal network by introduced animals. Issue 2 (15th September 2021) - Heleno, Ruben H.; Mendes, Filipa; Coelho, Ana P.; Ramos, Jaime A.; Palmeirim, Jorge M.; Rainho, Ana; de Lima, Ricardo F.
Abstract : Biological invasions are a major threat to global biodiversity with particularly deleterious consequences on oceanic islands. The introduction of large terrestrial animals – generally absent on islands – can disrupt important ecosystem functions, such as the dispersal of native seeds. However, while the consequences of plant invasions received much attention, the potential of introduced animals to change insular seed dispersal networks remains largely unknown. Here, we collated evidence from five sampling methods to assemble qualitative and quantitative, multi‐guild seed dispersal network for the island of São Tomé (Gulf of Guinea) and explore whether native and introduced seed dispersers consistently differ in their topological roles, in their gape width and in the size of the dispersed seeds. Our network included 428 interactions between 23 dispersers (14 birds, 2 bats, 1 snake and 6 non‐flying mammals) and 133 plant species. Each method (direct observations, identification of seeds in droppings and stomachs, questionnaires and literature review) was particularly informative for a small group of dispersers, thus rendering largely complementary information. Native and introduced dispersers did not differ in their topological position in either qualitative or quantitative networks (linkage level, specialization d' and species strength). However, introduced dispersers tend to have much larger gape widths and to disperse significantly larger seeds. Our results point to a general upsizing of the seed dispersal network in the island of São Tomé driven by the recent arrival of large, introduced animals. We argue that this pattern is likely common on other oceanic islands where introduced dispersers might counteract the general pattern of seed dispersal downsizing resulting from the selective extinction of larger animals.